2005
DOI: 10.1002/mame.200400237
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of Different Film Blowing Polyethylene Samples Under Shear and Elongational Flow

Abstract: Summary: The rheological behavior of polyethylenes is mainly dominated by the molecular weight, the molecular weight distribution and by the type, the amount and the distribution of the chain branches. In this work a linear metallocene catalyzed polyethylene (m‐PE), a branched metallocene catalyzed polyethylene (m‐bPE), a conventional linear low density polyethylene (LLDPE) and a low density polyethylene (LDPE) have been investigated in order to compare their rheological behavior in shear and in elongational f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…It is important to elucidate these aspects of molecular structure of polyolefins both in the production of polymers and their end‐use properties. It is well known that besides the dependence of the rheological behavior on external parameters such as shear rate and temperature, the rheological properties of polymer melts are strongly affected by the molecular structure 1–3. Since the rheological testing has its own advantage compared with gel permeation chromatography (GPC), temperature rising elution fractionation (TREF), 13 C‐NMR, etc, it is necessary to get some insight into the relationship between rheological properties and molecular characteristics of polyolefins 4…”
Section: Introductionmentioning
confidence: 99%
“…It is important to elucidate these aspects of molecular structure of polyolefins both in the production of polymers and their end‐use properties. It is well known that besides the dependence of the rheological behavior on external parameters such as shear rate and temperature, the rheological properties of polymer melts are strongly affected by the molecular structure 1–3. Since the rheological testing has its own advantage compared with gel permeation chromatography (GPC), temperature rising elution fractionation (TREF), 13 C‐NMR, etc, it is necessary to get some insight into the relationship between rheological properties and molecular characteristics of polyolefins 4…”
Section: Introductionmentioning
confidence: 99%
“…In the family of polyethylenes, metallocene linear low‐density polyethylene (mLLDPE) presents superior physical and mechanical properties as compared to polyethylenes with the same average molecular mass produced using conventional catalysts. However, due to its molecular characteristics (narrow distribution of molecular mass with short chain branching and homogeneous distribution of the chain branching), the processability of mLLDPE is poor,3–6 so a high melt pressure and a high motor load during the extrusion are required. Consequently the market penetration of mLLDPE has been much slower than predicted earlier.…”
Section: Introductionmentioning
confidence: 99%
“…Some papers dealing with mLLDPE/LDPE blends have been published, mostly reporting on miscibility, rheological, thermal and mechanical properties 5,6,8,11–21. In general, for a given molecular mass, all the quoted papers stated that in mLLDPE/LDPE blends the long chain branching is the primary factor controlling the rheological and processing behavior of polyethylenes.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to its molecular characteristics (narrow distribution of molecular mass with short chain branching and homogeneous distribution of the chain branching), the processability of mLLDPE is poor, [3][4][5][6] so a high melt pressure and a high motor load during the extrusion are required. Consequently the market penetration of mLLDPE has been much slower than predicted earlier.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Some papers dealing with mLLDPE/LDPE blends have been published, mostly reporting on miscibility, rheological, thermal and mechanical properties. [5,6,8,[11][12][13][14][15][16][17][18][19][20][21] In general, for a given molecular mass, all the quoted papers stated that in mLLDPE/LDPE blends the long chain branching is the primary factor controlling the rheological and processing behavior of polyethylenes. It is shown that the addition of small amounts of high molecular mass distribution PE to a narrow molecular weight distribution mLLDPE promotes higher recoverable shear or elasticity.…”
Section: Introductionmentioning
confidence: 99%